Efeitos dos danos mecânicos e fisiológicos na colheita e beneficiamento de sementes de soja - Lopes, Magnolia de Mendonca [UNESP]; Dedemo Prado, Mateus Oliveira; Sader, Rubens [UNESP]; Barbosa, Rafael Marani (Universidade Federal de Uberlândia (UFU), 2011)
The objective of this study was to evaluate the effect of mechanical damage and physiological events in harvesting and processing of soybean cv. Mosoy RR 8000. The samples were taken during harvest manual, mechanical harvesting and during processing (receipt, pre-cleaning, cleaning, spiral separator, classification and gravity table). The physiological and physical quality was analized through the purity, germination, vigor (first germination count, seedling dry matter, accelerated aging, electrical conductivity, tetrazolium, mechanical damages and seedling field emergence) tests. The statistical design used was a entirely randomized with nine treatments (9 sampling points) with 4 replications, being the means compared by the Tuckey test at 5% probability. In the purity and seedling field emergence were observed highly significative difference between the sampling process, also this differences were obtained the first germination count, seedling dry weight matter, accelerated aging and electrical conductivity which showed smaller results for the mechanical harvesting when compared with the manual harvesting. The germination was obtained differences at 5% for the manual harvesting in relation to the mechanical harvesting were obtained smaller results, being the main cause of reducing the soybean seed quality, when compared with the manual harvesting.

O objetivo deste trabalho foi o de avaliar os danos mecânicos ocorridos na colheita e no beneficiamento sobre a pureza, germinação, vigor e viabilidade de sementes de soja cv. Msoy 8000 RR. A qualidade física e fisiológica foi analisada por meio dos testes de pureza, germinação e vigor (primeira contagem da germinação, matéria seca de plântulas, envelhecimento acelerado, condutividade elétrica, tetrazólio, danos mecânicos e emergência em campo). Foi utilizado um delineamento inteiramente casualizado com nove pontos de coleta com quatro repetições, sendo as médias comparadas pelo teste de Tukey a 5% de probabilidade. Nos testes de pureza e emergência em campo foram obtidas diferenças altamente significativas entre as etapas de amostragem, sendo que esta diferença também foi verificada nos testes de vigor realizados (primeira contagem da germinação, matéria seca de plântulas, envelhecimento acelerado, condutividade elétrica), que de um modo geral apresentaram resultados menores para a colheita mecânica e o restante do processo, quando comparados à colheita manual.
Mechanical and fisiological effects on the harvesting and processing of soybean seeds
Keywords: Glycine max (L.) Merril; Injury; Germination; Vigor; viability; Tetrazolium